Innovative Research Methodologies in Management Volume I: Philosophy, Measurement and Modelling (Springer International Publishing, 2018)
A seminal collection of research methodology themes, this two-volume work provides a set of key scholarly developments related to robustness, allowing scholars to advance their knowledge of research methods used outside of their own immediate fields. With a focus on emerging methodologies within management, key areas of importance are dissected with chapters covering statistical modelling, new measurements, digital research, biometrics and neuroscience, the philosophy of research, computer modelling approaches and new mathematical theories, among others. A genuinely pioneering contribution to the advancement of research methods in business studies, Innovative Research Methodologies in Management presents an analytical and engaging discussion on each topic. By introducing new research agendas it aims to pave the way for increased application of innovative techniques, allow ing the exploration of future research perspectives. Volume I covers a range of research methodologies within the realms of philosophy, measurement and modelling, and focusses on meta-modern mixed methods such as neurophilosophy, diagnostic measurement, and emotivity and ephemera research.